STORAGE PERFORMANCE OF APPLE CULTIVARS HARVESTED AT DIFFERENT STAGES OF MATURITY - I. Jan; A. Rab; M. Sajid (Journal of Animal and Plant Sciences, 2012)
The experiment was conducted to study the effect of storage on quality parameters of apple cultivars harvested at different stages of maturity at Horticulture Postharvest Laboratory, KP Agricultural University, Peshawar-Pakistan during 2007-08. The fruits were harvested at three different stages of maturity at fifteen days interval representing early, mid and late harvesting stage from apple cultivars: Royal Gala, Mondial Gala, Golden Delicious and Red Delicious and evaluated for different quality parameters at 0 and 150 days storage at 5±10 0C with 60-70 % relative humidity. Cultivar Red Delicious had the highest ascorbic acid (12.49 mg/100g), firmness (5.85 kg/cm2) but also the bitter pit (14.22 %) and soft rot (15.52 %) incidence, while titratable acidity (0.56 %) was observed in cultivar Mondial Gala. The percent weight loss, total soluble solids, total sugar, bitter pit incidence and soft rot increased while, juice content, titratable acidity, ascorbic acid and firmness declined with increase in storage duration. The juice content (47.68 %), total soluble solids (10.07), total sugar (9.31 %), ascorbic acid (10.11 mg/100g) and soft rot (9.52 %) recorded with early mature fruit, increased to juice content (59.33 %), total soluble solids (12.92), total sugar (12.98 %), ascorbic acid (12.50 %) and soft rot (15.22 %) accordingly in late mature fruits, while weight loss (3.34 %), titratable acidity (0.59 %), firmness (5.88 kg/cm2), and bitter pit (11.69 %) recorded at early maturity stage, declined with delaying the harvesting to weight loss (1.93 %), starch score (3.21), titratable acidity (0.49 %), firmness (4.81 kg/cm2), density of fruit (4.81 g/cm3) and bitter pit (6.63 %) at late maturity stage.
Keywords: Apple; cultivars; storage; harvesting stage; weight loss; ascorbic acid; firmness; bitter pit; soft rot